2020
DOI: 10.3847/2041-8213/ab961d
|View full text |Cite
|
Sign up to set email alerts
|

GW190412 as a Third-generation Black Hole Merger from a Super Star Cluster

Abstract: We explore the possibility that GW190412, a binary black hole merger with a non-equal-mass ratio and significantly spinning primary, was formed through repeated black hole mergers in a dense super star cluster. Using a combination of semianalytic prescriptions for the remnant spin and recoil kick of black hole mergers, we show that the mass ratio and spin of GW190412 are consistent with a binary black hole whose primary component has undergone two successive mergers from a population of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 90 publications
3
56
0
1
Order By: Relevance
“…It is not clear if isolated stellar evolutionary models alone can consistently produce the c eff distribution in the detected events so far. Recent works by Rodriguez et al (2020) and Gerosa et al (2020) have also shown that it would be possible to reproduce these detections with repeated mergers of previous merger products in extremely large clusters. This would require that BHs are born with low natal spins, so as to retain more of the merger remnants.…”
Section: Spinsmentioning
confidence: 72%
See 2 more Smart Citations
“…It is not clear if isolated stellar evolutionary models alone can consistently produce the c eff distribution in the detected events so far. Recent works by Rodriguez et al (2020) and Gerosa et al (2020) have also shown that it would be possible to reproduce these detections with repeated mergers of previous merger products in extremely large clusters. This would require that BHs are born with low natal spins, so as to retain more of the merger remnants.…”
Section: Spinsmentioning
confidence: 72%
“…However, recent works by Rodriguez et al (2020) and Gerosa et al (2020) have shown that the relative fraction of low-mass-ratio merger events can be enhanced by second-and third-generation mergers in dynamical environments, producing GW190412-like events as a result, though analysis by Kimball et al (2020) casts doubt on the hierarchical merger scenario for GW190412. Due to the efficiency of mass segregation, the remnant of a previous merger is expected to be twice as massive as the 1G BHs in the cluster (see also Samsing & Hotokezaka 2020).…”
Section: Massesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is exceptional on account of its mass ratio, which is inferred as = -+ q 0.28 0.06 0.13 assuming the fiducial parameter estimation prior. The large difference in component masses would not be surprising for a hierarchical merger (Rodriguez et al 2020;Gerosa et al 2020), so here we investigate how our results change including GW190412. For this, we use parameterestimation results for GW190412 from Zevin et al (2020).…”
Section: Appendix B Including Gw190412mentioning
confidence: 97%
“…With a measured primary spin χ 1 ∼ 0.43 [3], GW190412 challenges previous predictions. Indeed, its unusual properties have already sparked numerous interpretations in the astrophysics community, ranging from isolated binaries with tidally spun-up secondaries [16][17][18] to dynamical assembly in young star clusters [19], gas-assisted migration in the disks of active galactic nuclei (AGN) [20], quadruple stars [21], and super star clusters [22].…”
Section: Introductionmentioning
confidence: 99%